Determination of lithic raw materials in Cantabrian Spain during Greenland Stadial 2: The Magdalenian of Tito Bustillo Cave (Ribadesella, Asturias). (December 2022) - Martín-Jarque, Sergio; Herrero-Alonso, Diego; Tarriño, Antonio; López-Tascón, Cristina; Prieto, Alejandro; Bécares, Julián; Álvarez-Fernández, Esteban
Highlights: Tito Bustillo 1c2 combines the raw materials, the debitage techniques and patterns, and the function of the tools. Data on the provenance of raw materials shows the high mobility of hunter-gatherer groups. Technological study indicates varying patterns in the management of the different raw materials. Typological study of flint assemblage shows the preference for laminar products reflected in the backed bladelets. Use-wear analysis documented activities that involved working mostly with hard animal matter and actions of short duration. Abstract: The lithic assemblage studied here comes from the space known as the Área de Estancia in Tito Bustillo Cave (Ribadesella, Asturias, Spain), a representative Magdalenian site. The remains were found in Sub-level 1c2 in the Lower Complex (1LC), which was excavated by J.A. Moure Romanillo from 1981 to 1983 and is associated with abundant evidence of osseous industry, fauna, portable art, etc. The present study is especially innovative because it introduces a holistic approach to the understanding of the management of lithic resources by hunter-gatherer groups in the late Pleistocene. It establishes the two main groups of raw materials in the assemblage (flint and quartzite) and the different types through a petrographic description, and the different procurement strategies that were employed. Some preliminary results about the functionality of these tools are also offered. The occupants of this cave during the Greenland Stadial 2 traced a diversified and complex dynamic of exploitation of lithic resources that combined both the most immediate, easily available and in greater volume (for example, quartzite and Piloña flint), and the most distant, of good knapping quality (Flysch flint, fundamentally). This circulation of raw materials is parallel to the patterns detected in other deposits in the region with a similar chronology. Significant differences are observed in the knapping schemes between raw materials based on the production of blanks for the manufacture of tools, whose typological classification and analysis of use-wear makes us propose a specialized and little diversified functionality, which is usually related to that of temporary occupations.